2016
DOI: 10.1007/978-3-319-41334-1_3
|View full text |Cite
|
Sign up to set email alerts
|

Emodin and Its Role in Chronic Diseases

Abstract: Diseases, such as heart disease, stroke, cancer, respiratory diseases, and diabetes, are by far the leading cause of mortality in the world, representing 60 % of all deaths. Although substantial medical advances have been made and many therapeutic approaches proposed yet traditional medicine and medicinal plants find an important place in therapy. They have been providing invaluable solutions to the various health problems. Emodin (1,3,8-trihydroxy-6-methylanthraquinone) is a natural anthraquinone derivative f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 151 publications
1
39
0
Order By: Relevance
“…21 Emodin has anti-inflammatory and antibacterial, antioxidant and antiviral efficacys. 22 A research displayed that emodin restrained airway inflammatory damage in mouse. 23 Other research proposed that emodin could reduce the inflammatory response caused by influenza A virus by restraining the levels of inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…21 Emodin has anti-inflammatory and antibacterial, antioxidant and antiviral efficacys. 22 A research displayed that emodin restrained airway inflammatory damage in mouse. 23 Other research proposed that emodin could reduce the inflammatory response caused by influenza A virus by restraining the levels of inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-cancer effect of emodin has been reported in several types of cancer; however, the development of novel therapeutic strategies for cancer treatment is required [ 27 ]. In particular, various reports have shown that emodin decreases HCC growth through the suppression of oncogenic growth signaling, such as the MAPK, PI3K-AKT, and STAT3 pathways, in both in vitro and in vivo models [ 9 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…105 For example, apigenin from Epimedium koreanum Nakai, emodin from Rheum palmatum L, quercetin from Hypericun ascyron L and curcumin from Curcuma louga L are all reported to modulate various chronic diseases within safe dose range. [106][107][108][109] Here in this article, we systematically review the existing literature concerning coptisine's diverse beneficial properties, and this continues to support the recommendation that coptisine can be applied to the treatment for cancer, inflammation, CVDs and metabolic disorders.…”
Section: Future Pros Pec Tsmentioning
confidence: 98%